TJNPR 2019
DOI: 10.26538/tjnpr/v3i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-Ulcer Properties of the Stem-Bark Fractions of Khaya senegalensis (Desr.) A. Jussin Albino Rats

Abstract: Article history:preliminary evaluation of crude methanol stem-bark extract of the plant revealed potent antiulcer properties. 21 Although much progress has been made in the management of H. pylori infection in gastric ulcer due to the widespread use of antisecretory drugs and antibiotics, increasing antimicrobial resistance has posed a great threat to its eradication. 22 Furthermore, emerging causes of peptic ulcers other than H. pylori and NSAIDs are imposing diagnostic and therapeutic challenges. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Fractions (aqueous methanol, hexane and ethyl acetate) of the plant's crude methanol extract were found to significantly lower gastric ulcer indices at 400 and 800mg/kg when compared with ethanol treated group. The findings strongly suggested Khaya senegalensis has anti-ulcerative properties, which could be due to its anti-secretory and antioxidative activities reported in the study [39]. Investigation of the effect of piroxicam co-administration with ethanol stem-bark extract of Khaya senegalensis on gastrotoxicity in rats also showed that, the interaction of plant extract with piroxicam resulted in the gastroprotective beneficial effects [40].…”
Section: Anti-ulcer Activitymentioning
confidence: 81%
“…Fractions (aqueous methanol, hexane and ethyl acetate) of the plant's crude methanol extract were found to significantly lower gastric ulcer indices at 400 and 800mg/kg when compared with ethanol treated group. The findings strongly suggested Khaya senegalensis has anti-ulcerative properties, which could be due to its anti-secretory and antioxidative activities reported in the study [39]. Investigation of the effect of piroxicam co-administration with ethanol stem-bark extract of Khaya senegalensis on gastrotoxicity in rats also showed that, the interaction of plant extract with piroxicam resulted in the gastroprotective beneficial effects [40].…”
Section: Anti-ulcer Activitymentioning
confidence: 81%